Developing of Authentic Assessment for Reading Comprehension on Blended Learning at Senior High School - Febrianirmala; Yulmiati; Rika Afrianti (Merwinspy Publisher, 2024)
The purpose of this study was to produce an authentic assessment of reading comprehension in Blended learning that is valid on narrative text and analytical exposition text at SMA N 12 Padang. So that the product can be used as a source of learning English, especially narrative text and exposition analytical text material. This type of research is research and development (R&D) with the development model proposed by Plomp (2013). The stages used in this development model are only one stage, namely the prototyping phase which doubles as a validity test. The research instrument used was a self-evaluation and validity sheet which self-evaluation analyzes the conformity of the product with the criteria of authentic assessment, reading comprehension, and blended learning. Based on the validator's evaluation, the results of the validity of the authentic assessment product were obtained at 83.8% reading comprehension with a very valid category. It means that the authentic assessment for reading comprehension in Blended learning on narrative text and analytical exposition text material at SMA N 12 Padang is stated to be valid and can be used by teachers and students.